Produção de insumos para o imunodiagnóstico da neosporose - Pacheco, Diene de Borba (2014)
Neosporosis is a disease caused by the apicomplexan parasite Neospora caninum, which is closely related to Toxoplasma gondii. N. caninum infection represents an important cause of reproductive failure in sheep, goats, horses, and cattle worldwide. The diagnosis of neosporosis is based on the detection of pathogen-specific antibodies in animal sera or the presence of tissue cysts. However, morphological similarities and serological cross-reactivity between N. caninum and T. gondii can result in the misdiagnosis. In this study, the N. caninum tachyzoite surface protein Ncp-43 was expressed in a recombinant form to elicit polyclonal antibodies (pAb) response. The pAb was purified and conjugated to horseradish peroxidase (HRP) or fluorescein isothiocyanate (FITC) to detect the recombinant and native Ncp-43 proteins, respectively. The pAb and pAb/HRP were able to recognize rNcp-43 by Dot blot and ELISA, and pAb/FITC immunolabeled the apical complex of tachyzoites. A blocking enzyme-linked immunosorbent assay (b-ELISA) was performed to evaluate pAb/HRP as a diagnostic tool. The mean percent inhibition for the positive and negative serum samples from cattle with neosporosis was significantly different (P < 0.0001). These results suggest that the pAb may bind to the same epitopes of Ncp-43 as anti-N. caninum antibodies in the positive samples tested. The b-ELISA using the pAb/HRP can facilitate diagnostic testing for neosporosis, since fewer steps are involved and cross-reactivity with secondary antibodies is avoided. In summary, this report describes the production of antibodies against N. caninum, and evaluates the potential of these tools for the development of new diagnostic tests for neosporosis.